Management Background and Release Conditions Structure Post-release Movements in Reintroduced Ungulates - Mertes, Katherine; Stabach, Jared A.; Songer, Melissa; Wacher, Tim; Newby, John; Chuven, Justin; Al Dhaheri, Shaikha; Leimgruber, Peter; Monfort, Steven (Frontiers in Ecology and Evolution, 2019)
One of the greatest challenges in restoring species to the wild is insufficient knowledge about their habitat requirements and movement ecology. This is especially true for wide-ranging species such as the scimitar-horned oryx (Oryx dammah). Once widespread across Sahelo-Saharan grasslands, oryx were declared Extinct in the Wild in 1999. Here, we integrate GPS/satellite tracking, remote sensing, and movement analyses to assess how reintroduced oryx respond to wild conditions. We monitored two groups of oryx, reared under different captive management regimes and released in different seasons, for 12 months after release. Our study provides the first movement trajectories and home range estimates for this species. We expected oryx movements after release to represent trade-offs between risky, energetically expensive exploration and resource exploitation. Oryx raised under semi-free ranging conditions and released during the wet season (“ranging”) exhibited this pattern of exploration followed by home range establishment. In contrast, oryx raised in small pens and released during the dry season (“penned”) explored far less novel terrain. Ranging oryx exhibited seasonal shifts in activity and movement timing, while penned oryx simply reduced overall movement and continuously accessed supplemental food and water. Sahelian ecosystems exhibit strong seasonal cycles and extensive spatial variation. In this highly variable environment, reintroduced oryx will need to disperse from the release site to acquire adequate forage throughout the year. Thus, we experimentally varied acclimation period, and expected dispersal to decrease with acclimation period length. Post-release dispersal ranged from 2 to 90 km: ranging oryx acclimated for ca. 6 months moved 40–60 km from the release site, while penned oryx acclimated for ca. 1 month remained within 5–25 km. Our results demonstrate that captive management and environmental conditions at release strongly influence the extent to which reintroduced oryx disperse and adapt to wild conditions. We also show that—in contrast to previous studies—longer acclimation periods do not necessarily lead to site fidelity. Finally, our findings demonstrate the importance of tracking a large proportion of reintroduced individuals to (1) accurately record post-release behaviors and vital rates, and (2) adaptively evaluate pre- and post-release management actions to improve conservation outcomes.